Sensory image in Umayyad poetry The book (Umayyad poets) as a model: (An analytical study) - Hassan, Huda Ahmed; Abbas, Saja Jassim Muhammad (Al-Adab Journal, 2023)
The sensory image is one of the most important means in highlighting the features of the poetic image, as through it the meanings are transmitted to the mind of the recipient and through it, he can understand the text in a more beautiful and clear way. Because it contains wonderful rhetorical images such as similes, metaphors, metaphors and euphemisms, in addition to sensory images, each of these images has a role that helps to strengthen and embody the meaning. Based on this importance, in our research, we deliberately monitored the sensory image in the aforementioned book, and how these poets were able to employ these images with unique poetic prowess and high stylistic sobriety.